KOMPETENSI KOMUNIKASI DOSEN DAN KONSEP DIRI MAHASISWA TERHADAP PRESTASI AKADEMIK MAHASISWA - Taufik Suprihatini (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2017)
Students less fully aware of the existence of themselves as the next generation and the future of the nation reflection. Consciousness as an independent, full responsibility mature human yet fully visible in the figure of the students, so the motivation for achievement sometimes not realized. They are often seen involved in the demonstrations, fights, involved in the activities of political organizations, even unconsciously they entered in forbidden religious organizations. The sample of this research is the students of Communication Science FISIP Undip class in 2013 and 2014 with a sampling technique using proportional random sampling technique, which will take 15% of the number of students. The researcher conducted a sample calculation using the formula of Frank Lynch.1 The variable research are the Lecturer Communication Competence and Self-Concept of Student as independent variables, the Student Academic Achievement as the dependent variable. Based on statistical test by using Pearson correlation and multiple correlation using SPSS version 21 indicates that there is no relationship between the variables of communication competence of lecturers, and students’ academic achievement. It can be seen from the significant value of both variables showed the 0.784> 0.05. So Ho accepted and Ha rejected. Student self-concept variables are not related to students’ academic achievement. It can be seen from the significant value of both variables that showed the number 0.998> 0.05. Then Ho accepted and Ha rejected. From the results of research conducted by Erli Zaenal about the factors were associated with grade point of Third Semester Midwifery Student of Health Polytechnic Bengkulu, it is known that academic achievements are influenced by internal factors and external factors. Internal factors include intelligence, motivation, habits, anxiety, interests and so on. While external factors include a family environment, school environment, community, socio-economic situation, and so on.